JON M. CHU’S FILM CRAZY RICH ASIANS: THE INTERPLAY OF WESTERN AND EASTERN CULTURES - I Gusti Ngurahe Ade Wiraldy; Daniel Ginting (LET: Linguistics, Literature and English Teaching Journal, 2021)
The film Crazy Rich Asians released in 2018 represents a complexity of social interactions among people with different cultural background. The adaptability to new environments is not always easy; yet, the main character is persistent and capable of maintaining her identity. Being an American born Chinese, Rachel Wu, the main character is depicted as a "banana". --yellow on the outside, white on the inside. Feeling like a curse to feel like an outsider in both the country, the main character was born in or the one her parents come from. The article aims to sketch the profile of Rachel Wu as a thoughtful, moderate person when dealing with other figures from a society that is exclusively oriented to traditional norms